Strengthening the postgraduate journey - Ibrahim, Norkasihan (Faculty of Pharmacy, 2025)
This session offers a safe and structured rehearsal platform to help PGs understand panel expectations, identify weaknesses early, and strengthen the overall quality of their research proposals. Held two weeks before the final DRP each semester, this session allows students to provide constructive, respectful, and peer-led feedback, guided by lecturers.